2012
DOI: 10.1016/j.chom.2012.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Extracellular Traps Mediate a Host Defense Response to Human Immunodeficiency Virus-1

Abstract: Neutrophils contribute to pathogen clearance by producing neutrophil extracellular traps (NETs), which are genomic DNA-based net-like structures that capture bacteria and fungi. Although NETs also express antiviral factors, such as myeloperoxidase and α-defensin, the involvement of NETs in antiviral responses remains unclear. We show that NETs capture human immunodeficiency virus (HIV)-1 and promote HIV-1 elimination through myeloperoxidase and α-defensin. Neutrophils detect HIV-1 by Toll-like receptors (TLRs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
509
1
16

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 605 publications
(573 citation statements)
references
References 43 publications
20
509
1
16
Order By: Relevance
“…In recent years their antimicrobial spectrum has been broadened by demonstration of their involvement in defense against HIV-1 [97], mycobacteria [68] and parasites such as malaria [85] and Leishmania [75,82].…”
Section: Participation Of Pmn In Vital Function Other Than Defense Agmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years their antimicrobial spectrum has been broadened by demonstration of their involvement in defense against HIV-1 [97], mycobacteria [68] and parasites such as malaria [85] and Leishmania [75,82].…”
Section: Participation Of Pmn In Vital Function Other Than Defense Agmentioning
confidence: 99%
“…NETs were shown to kill various bacteria and Candida albicans [15,110] but most recently they were reported to be also involved in defense against human immunodeficiency virus [97]. The mechanism of microbe elimination is not fully understood but probably relies on multiple parallel pathways.…”
Section: Extracellular Killing By Neutrophilsmentioning
confidence: 99%
“…These comprise cell shape changes, CD62L shedding, priming for enhanced respiratory burst 17,[47][48][49] , chemotaxis, phagocytosis 17,50 and neutrophil extracellular trap formation induction 51 , lipid mediator production 18 , prolonged survival 49,52 and cytokine production (using, however, less pure neutrophil populations than in this study), including TNFa 53 and IL-6 (refs 48,53,54). Similarly, two studies 55,56 have reported that human neutrophils cultured in the presence of infectious respiratory syncytial virus produce IL-6 at 1 ng ml À 1 per 5 Â 10 6 cells per 3 h (498% neutrophil purity 55 ), or at 100 pg ml À 1 per 5 Â 10 5 cells per 12 h (497% purity 56 ).…”
Section: Il-6 Production By Murine Neutrophils In Vitro and In Vivomentioning
confidence: 99%
“…An increasing number of bacteria, fungi, viruses and protozoan parasites have been shown to induce NETs (Brinkmann et al, 2004;Guimarães-Costa et al, 2009;Urban et al, 2009;Saitoh et al, 2012;Jenne et al, 2013) but to date only three fungal species (Candida albicans, Aspergillus spp. and Cryptococcus gattii) have been reported to activate their production (Urban et al, 2006;Bruns et al, 2010;Springer et al, 2010;Bianchi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%